Фармакоэкономический анализ использования лираглутида в составе комбинированной терапии в лечении сахарного диабета 2-го типа - A. Yu. Kulikov; I. V. Novikov (IRBIS LLC, 2015)
The analysis goal is to determine the cost-effectiveness of liraglutideas add-on to metformin in for patients with type 2 diabetes in condition of the Russian health care system. Total medical expenses and effectiveness in terms of QALY are compared for liraglutide, glimepiride and rosiglitazone, all in combination with metformin, and metformin monotherapy. Methods: Data were sourced from a clinical trial comparing liraglutide vs. glimepiride (in combination with metformin), and a clinical trial comparing liraglutide vs. rosiglitazone (as add-on to metformin). From them data on clinical effectiveness in form of impact on HbA1(c), body mass index and blood pressure are extracted. Utility values are mostly taken from the UK Prospective Diabetes Studies supplemented with other published sources. The analysis is conducted from the perspective of the Russian health care system. Respectively the cost of the following resources is accounted: comparing of alternatives, concomitant pharmacotherapy, cost of medical manipulation, cost of ambulatory visits. Both future costs and clinical benefits are discounted at 3 percent. Sensitivity analysis is performed. Results of this analysis are shown in the incremental cost-utility rate (ICUR). Results: the data of the analysis illustrates that liraglutide therapy for type 2 diabetes patients provides a significant health improvement from the perspective of quality adjusted life-years. Simultaneously liraglutide demonstrates better cost-effectiveness than the compared alternatives. The ICUR index of 1.2 mg liraglutide in combination with metformin equal to 1 348368 rub, 1 161874 rub and 537331 rub for QALY in comparison with metformin monotherapy, glimepiride and rosiglitazone, both in combination with metformin, respectively. Conclusions: liraglutide 1,2 mg has turned to be cost-effective therapeutic alternative for treatment of type 2 diabetes in adult patients in conditions of Russian health care system over a 10-year time horizon.